Perceptions and practices related to birthweight in rural Bangladesh: Implications for neonatal health programs in low- and middle-income settings. - Monjura Khatun Nisha; Camille Raynes-Greenow; Aminur Rahman; Ashraful Alam (PLoS ONE)
Background Globally, low birthweight (LBW) infants (<2.5 kilograms) contribute up to 80% of neonatal mortality. In Bangladesh, approximately 62% of all births occur at home and therefore, weighing newborns immediately after birth is not feasible. Thus, estimates of birthweight in Bangladesh are mostly obtained based on maternal perception of the newborn's birth size. Little is known about how birthweight is perceived in rural communities, and whether families associate birthweight with newborn's health status. Our objective was to explore families' perceptions of newborn's birthweight, and preventive and care practices for a LBW newborn in rural Bangladesh. Methods We conducted a qualitative study in two rural settings of Bangladesh, including 32 in-depth interviews (11 with pregnant women, 12 with recently delivered women, 4 with husbands whose wives were pregnant or had a recent birth, 5 with mothers-in-law whose daughters-in-law were pregnant or had a recent birth), 2 focus group discussions with husbands and 4 key-informant interviews with community health workers. We used thematic analysis to analyse the data. Results Most participants did not consider birthweight a priority for assessing a newborn's health status, although there was a desire for a healthy newborn. Recognition of different categories of birthweight was subjective and often included several physical descriptors including birth size of the newborn. LBW was not considered as a criterion of a newborn's illness unless the newborn appeared unwell. Maternal poor nutrition, inadequate diet in pregnancy, anaemia, illness during pregnancy, short stature, twin births and influence of supernatural spirit were identified as the major causes of LBW. Women's preventive practices for LBW or small newborns were predominantly constrained by a lack of awareness of birthweight and fear of caesarean section. As an effort to avoid caesarean section during birth, several women tended to perform potentially harmful practices in order to give birth to a small size newborn; such as avoiding nutritious food and eating less in pregnancy. Common practices to treat a LBW or small newborn who appeared ill included breastfeeding, feeding animal milk, feeding sugary water, feeding formula, oil massage, keeping the small newborn warm and seeking care from formal and informal care providers including a spiritual leader. Maternal lack of decision-making power, financial constraint, home birth and superstition were the major challenges to caring for a LBW newborn. Conclusion Birthweight was not well-understood in the rural community, which highlighted substantial challenges to the prevention and care practices of LBW newborns. Community-level health education is needed to promote awareness related to the recognition of birthweight in rural settings.